2016
DOI: 10.1007/jhep08(2016)037
|View full text |Cite
|
Sign up to set email alerts
|

Natural NMSSM after LHC Run I and the Higgsino dominated dark matter scenario

Abstract: Abstract:We investigate the impact of the direct searches for SUSY at LHC Run I on the naturalness of the Next-to-Minimal Supersymmetric Standard Model (NMSSM). For this end, we first scan the vast parameter space of the NMSSM to get the region where the fine tuning measures ∆ Z and ∆ h at the electroweak scale are less than about 50, then we implement by simulations the constraints of the direct searches on the parameter points in the region. Our results indicate that although the direct search experiments ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 106 publications
(156 reference statements)
1
46
0
Order By: Relevance
“…While for the samples with h 1 corresponding to the SM-like Higgs boson, they satisfy µ 450GeV with µ m χ 0 1 or m m χ 0 1 . These features entail following conditions for the samples to be consistent with the experimental constraints: moderately strong cancellation between the h 1 and h 2 contributions to the SI cross section, |N 13 | 2 |N 14 | 2 as well as the suppressed spectrum of the sparticles with χ 0 1 [54,57] 3 .…”
Section: Numerical Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…While for the samples with h 1 corresponding to the SM-like Higgs boson, they satisfy µ 450GeV with µ m χ 0 1 or m m χ 0 1 . These features entail following conditions for the samples to be consistent with the experimental constraints: moderately strong cancellation between the h 1 and h 2 contributions to the SI cross section, |N 13 | 2 |N 14 | 2 as well as the suppressed spectrum of the sparticles with χ 0 1 [54,57] 3 .…”
Section: Numerical Resultsmentioning
confidence: 72%
“…We checked the properties of these samples and found that they have been excluded by the 3 + E miss T search at the LHC [102]. [54]. We checked that the main annihilation channels of the DM in early universe include χ 0…”
Section: Singlino-dominated Dmmentioning
confidence: 99%
See 1 more Smart Citation
“…On the theoretical side, Z/h resonant annihilation is important in natural SUSY [37], especially in the natural MSSM, since it allows the lightest neutralino to achieve the observed thermal relic density [38]. In the natural Next-to-MSSM (NMSSM), although the inclusion of a singlet superfield relaxes the experimental constraints on the electroweakinos, the exclusion of the Z/h funnel region increases the lower limit on the DM mass from 20 GeV to 80 GeV [39][40][41]. The lower limit on the DM mass, in turn, is critical for any LHC sparticle search because under R-parity all sparticles decay to the lightest supersymmetric particle (LSP)χ 0 1 and the LSP mass is folded into the analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]). In this paper, we reanalyze the question: does the non-observation of SUSY particles make any minimal realization of a supersymmetric SM necessarily an unnatural theory?…”
Section: Introductionmentioning
confidence: 99%